OPTIMALISASI PENENTUAN RUTE DISTRIBUSI PUPUK UNTUK MEMINIMALKAN BIAYA TRANSPORTASI DENGAN METODE SAVING MATRIX - Akhmad Sutoni; Iman Apipudin (Universitas Ahmad Dahlan Indonesia, 2019)
Product delivery must be in accordance with customerdemand in a timely and efficient manner. So that thedistribution process does not result in waste of time,distance, and energy. CV. XY is engaged in trading theneeds of agricultural materials having problems in thedistribution process. The sender's route itself changes overtime depending on the driver's wishes. So there will be manydifferent routes with one goal each. The goal is to produce alonger shipping path, without first looking at vehiclecapacity and the distance that must be traveled. This resultsin expensive transportation costs. From data processingdistribution using the Matrix Saving method obtained 4 newroutes, namely Route 1 (DC - CUS 3 - CUS 10 - CUS 8 -CUS 6- DC), Route 2 (DC - CUS 4 - CUS 2 - CUS 7 - DC) ,Route 3 (DC - CUS 5 - CUS - 9 - CUS 11 - DC), Route 4(DC - CUS 1 - CUS 12 - DC). Distance saving and costefficiency were obtained from 8 routes to 4 routes and totaldistance saving of 39.1 km. Saving in transportation costs ofRp. 12,825,120 or 50% per month.